THE EFFECTIVENESS OF CONGKLAK TRADITIONAL GAME TO IMPROVE STUDENTS LEARNING MOTIVATION IN HUMAN EXCRESSION SYSTEM MATERIALS - Ucik Nurdiana; Wahono Widodo (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2019)
The research aims to investigate the effectiveness of congklak game media as a learning media that can improve students learning motivation on the chapter of Human Excretion System. This research was conducted by using one group pretest-posttest design that tested on 15 students of VIII class 32 Surabaya State Junior High School. The instruments that used is a questionnaire of student motivation which distributed to students before and after learning using traditional congklak game media and student activity observation sheet which filled by observers during the learning. The results which is obtained from motivation questionnaire can be known that Gain Score on the aspects of attention and satisfaction is 0.4 with medium criteria. While on relevance and satisfaction aspect is 0,3 with medium criteria. Based on students' activity data show that from meeting 1 to 4 students' irrelevant behavior is decrease and students' relevant behavior is increase.. This showed that students are increasingly motivated to do learning. It can be concluded that the traditional game media Congklak effective to increasing student learning motivation.Keywords: learning media, congklak game, learning motivation